2016
DOI: 10.21037/jtd.2016.05.98
|View full text |Cite
|
Sign up to set email alerts
|

Surgery of colorectal cancer lung metastases: analysis of survival, recurrence and re-surgery

Abstract: Background: Surgery is considered an effective therapeutic option for patients with lung metastasis (MTS) of colorectal cancer (CRC). The purpose of the study was to evaluate efficacy and feasibility of lung metastasectomy in CRC patients and to explore factors of prognostic relevance. Methods: This is a retrospective study of patients operated for lung MTS of CRC from 2004 to 2012 in a single Institution. Overall survival (OS) was the primary endpoint. Secondary endpoints were progression free survival (PFS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 24 publications
3
42
0
4
Order By: Relevance
“…Colorectal cancers have very high rates of relapses (Guerrera et al, 2016). However, minimal interventions are available, in response to, possible relapse of the cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colorectal cancers have very high rates of relapses (Guerrera et al, 2016). However, minimal interventions are available, in response to, possible relapse of the cancers.…”
Section: Discussionmentioning
confidence: 99%
“…It is mostly a relapsed cancer that is responsible for the major deaths of the cancer patients. Colorectal cancers have very high rates of relapses (Guerrera et al, 2016). Moreover, it is now known that cancer stem cells-CSCs/tumour initiating cells-TICs are the ones that form the bulk of a relapsed tumour (Yu et al, 2016b).…”
Section: Discussionmentioning
confidence: 99%
“…Complete palpation was deemed fundamental for the purpose of the study; consequently, patients undergoing video-assisted thoracic surgery were excluded from the cohort for this study. Additional preoperative patient assessment, surgical approach, and surgical technique were accomplished as previously described [9,14]. Concerning lymph node evaluation, N1 and N2 stations were determined according to the International Association for the Study of Lung Cancer lymph nodal map [15].…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, among alternative metastasisdirected local treatments, minimally invasive surgery (video-assisted thoracic surgery), stereotactic body radiotherapy, and radiofrequency ablation, with or without systemic chemotherapy [4,5], are commonly proposed to CRC metastatic patients in routine clinical practice [6]. Furthermore, a copious amount of literature has indicated that, in CRC patients undergoing lung metastasectomy or local treatment, certain factors, including lymph node involvement (LNI) and number of pulmonary metastases, are consistent predictors of the outcome [3,[7][8][9][10][11].…”
mentioning
confidence: 99%
“…[3][4][5] In Denmark, these three treatment modalities constitute an integral part of the multidisciplinary treatment of mCRC. The majority of literature supporting the use of metastases directed therapy consists of single institution experiences for both resection, 6,7 RFA 8,9 and SBRT 10,11 demonstrating a potential of curability for subsets of patients. Liver resection remains the most extensive studied treatment with a recent meta-analysis of 54 singled arm studies demonstrating a 5-and 10-years overall survival of 38% and 26%, respectively.…”
mentioning
confidence: 99%